Magnesium aluminate spinel micro-nano fiber as well as preparation method and infrared stealth application thereof

Magnesium aluminum spinel micro-nanofibers were prepared through electrospinning technology and heat treatment technology, which solved the shortcomings of existing infrared stealth materials in infrared detection technology, achieved low infrared emissivity and excellent optical performance, and expanded its weapons and equipment and applications in the field of aerospace.

CN119221155APending Publication Date: 2024-12-31ARMY ENG UNIV OF PLA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311585171.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-11-24
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing infrared stealth materials still pose a great threat to infrared detection technology, especially for high-power engine aircraft, ships and combat vehicles and other equipment, the magnesium-aluminum spinel powder has limited capabilities in infrared stealth and needs to be improved.

Method used

Electrospinning technology combined with heat treatment technology to prepare magnesium aluminum spinel micro-nanofibers. By mixing aluminum nitrate, magnesium nitrate, citric acid solutions with PVP glacial acetic acid solution, adjusting pH and calcining, magnesium with a diameter of 200-700nm is produced. Aluminum spinel micro-nanofibers have unique morphological structure and low infrared emissivity.

Benefits of technology

The prepared magnesium aluminum spinel micro-nanofibers have excellent infrared transmittance and low infrared emissivity. As a more excellent infrared stealth material, they have broad application prospects in the fields of weapons and equipment stealth, aerospace, etc.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119221155A_ABST
    Figure CN119221155A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of infrared stealth materials, and particularly relates to a magnesium aluminate spinel micro-nanofiber as well as a preparation method and infrared stealth application thereof. According to the magnesium aluminate spinel micro-nanofiber provided by the invention, the magnesium aluminate spinel micro-nanofiber is prepared by combining an electrostatic spinning technology with a heat treatment process, and the prepared magnesium aluminate spinel micro-nanofiber has a unique morphology structure by controlling parameters such as PVP (Polyvinyl Pyrrolidone) concentration and the like; the material can be used as a more excellent infrared stealth material with low infrared emissivity, and has a wide application prospect in the fields of weapon stealth, aerospace, chemical engineering and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of infrared stealth materials, and specifically relates to a magnesium aluminum spinel micro-nano fiber and a preparation method and infrared stealth application thereof. Background Art

[0002] With the development of multi-mode composite guidance technology and detection technology, radar, infrared, laser and visible light detection methods will pose a threat to weapons and equipment on the battlefield. Among them, infrared detection is a detection technology that is currently being developed. With the continuous emergence of high-precision and high-resolution infrared detectors, it has developed rapidly, posing a great threat to military facilities and weapons and equipment, especially aircraft, ships and combat vehicles with high-power engines. In order to improve the combat and survivability of weapons and equipment, it is of great significance to develop infrared stealth materials. Magnesium aluminum spinel (MgAl 2 O 4 ) is an important AB 2 O 4 Isometric compounds have a face-centered cubic lattice structure and belong to O h 7 (Fd3m, 227) space group. MgAl 2 O 4 It has high hardness (Mohs hardness 8.0), good corrosion resistance, optical isotropy, no birefringence, and high transmittance from ultraviolet to mid-infrared bands (0.25-5.5μm). It is a transparent ceramic material with excellent mechanical properties and excellent optical properties. It has important application value in missile guidance system window materials, transparent bulletproof armor, and infrared sensors for ships and submarines. At present, domestic and foreign research mainly focuses on the preparation of high-performance magnesium-aluminum spinel powders with high purity and narrow particle size distribution. It has certain capabilities in infrared stealth, but there is still much room for improvement. Summary of the invention

[0003] In view of the above problems, the present invention provides a magnesium aluminum spinel micro-nano fiber and its preparation method and infrared stealth application. The magnesium aluminum spinel micro-nano fiber prepared by the preparation method provided by the present invention has a unique morphology and structure, low infrared emissivity, and can be used as a more excellent infrared stealth material.

[0004] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical scheme:

[0005] In a first aspect, the present invention provides a method for preparing magnesium aluminum spinel micro-nano fibers, comprising the following steps:

[0006] S1. Dissolve aluminum nitrate, magnesium nitrate and citric acid in water, adjust the pH of the resulting solution to 6.5-7.5, react for at least 10 hours, and then concentrate to a viscous sol;

[0007] S2, uniformly mixing the viscous sol-like reactant obtained in S1 with the glacial acetic acid solution of PVP, so that the PVP concentration in the mixed solution is 0.35-0.45 g / mL, to obtain a spinning precursor solution;

[0008] S3, electrospinning the spinning precursor solution at a voltage of 16-18 kV and a needle of 22 # Stainless steel needle, the distance between the needle and the receiving plate is 14-16cm, and MgAl 2 O 4 / PVP composite fiber;

[0009] S4, the MgAl 2 O 4 The / PVP composite fiber was heated to 650-800°C at a rate of 0.8-1.2°C / min and calcined for 2h, and then naturally cooled to room temperature.

[0010] The preparation method provided by the present invention can produce magnesium aluminate spinel micro-nano fibers with a diameter of 200 to 700 nm. The obtained magnesium aluminate spinel micro-nano fibers have a smooth surface and a unique morphological structure compared to the magnesium aluminate spinel powder in the prior art, which enables them to produce specific properties different from powder materials and can be used as a more excellent infrared stealth material with low infrared emissivity.

[0011] In this preparation method, the concentration of PVP in S2 ensures that the resulting composite fiber has a round shape with a smooth surface and uniform thickness. If the PVP concentration is too low, more "spindles" will be present in the composite fiber, and if the PVP concentration is too high, it will cause fiber adhesion.

[0012] Under the heating condition of more than 650℃ in S4, PVP, nitrate, acetate groups, residual solvent and other volatiles in the composite fiber are removed to form pure spinel structure MgAl 2 O 4 , and with the increase of calcination temperature, MgAl 2 O 4 As the grain size increases, the crystallinity improves and the crystal structure becomes more complete.

[0013] In combination with the first aspect, the molar ratio of aluminum nitrate, magnesium nitrate and citric acid is 2:1:4.

[0014] In combination with the first aspect, in S1, the pH of the obtained solution is adjusted with aqueous ammonia.

[0015] In combination with the first aspect, the PVP concentration in S2 is preferably 0.4 g / mL to obtain better morphology.

[0016] In combination with the first aspect, the voltage in S3 is preferably 17 kV, and the distance between the needle and the receiving plate is preferably 15 cm.

[0017] In combination with the first aspect, the calcination temperature in S4 is 650-750°C.

[0018] In a second aspect, the present invention further provides a magnesium aluminum spinel micro-nano fiber, which is made according to the above preparation method.

[0019] In a third aspect, the present invention provides the use of the above-mentioned magnesium aluminum spinel micro-nano fiber in the preparation of infrared stealth material. The magnesium aluminum spinel micro-nano fiber prepared by the above method has a diameter of 200-700nm, a smooth surface, and a high infrared transmittance, and can be used as a more excellent infrared stealth material with low infrared emissivity.

[0020] In a fourth aspect, the present invention provides an infrared stealth material, the raw materials of which include the above-mentioned magnesium aluminum spinel micro-nano fibers.

[0021] In conjunction with the fourth aspect, the infrared stealth material includes a film and a coating. The magnesium aluminum spinel micro-nano fiber can be made into a film with excellent optical properties, or made into a coating, which can be applied to the surface of an object by spraying, brushing, etc. to achieve an infrared stealth effect.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] The present invention adopts electrospinning technology combined with heat treatment process to prepare magnesium aluminum spinel micro-nano fibers. The obtained magnesium aluminum spinel micro-nano fibers have a diameter of 200-700nm and a smooth surface. Compared with the magnesium aluminum spinel powder in the prior art, the magnesium aluminum spinel micro-nano fibers have a unique morphology and structure, and can be used as a more excellent infrared stealth material with low infrared emissivity. It will have broad application prospects in the fields of weapon equipment stealth, aerospace, chemical industry, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 MgAl in Test Example 1 of the present invention 2 O 4 DSC-TGA curve of / PVP composite fiber;

[0025] Figure 2 MgAl in Test Example 1 of the present invention 2 O 4 / PVP composite fibers were not calcined and heated at 1℃·min -1 XRD patterns after calcination at a rate of 700℃, 800℃, 900℃, 1000℃, 1200℃ and 1500℃ respectively;

[0026] Figure 3 The MgAl2O3 calcined at 700°C in Test Example 1 of the present invention is 2 O 4 FT-IR images of micro-nanofibers;

[0027] Figure 4 MgAl prepared with different PVP mass concentrations in Test Example 1 of the present invention 2 O 4 SEM photos of / PVP composite fibers;

[0028] Figure 5 This is a SEM photograph obtained by scanning electron microscope on the magnesium aluminum spinel micro-nano fiber prepared in Example 2 in Test Example 1 of the present invention;

[0029] Figure 6 This is a SEM photo obtained by scanning the electron microscope on the product obtained in Comparative Example 3 in Test Example 1 of the present invention;

[0030] Figure 7 This is a SEM photo obtained by scanning the electron microscope on the product obtained in Comparative Example 5 in Test Example 1 of the present invention;

[0031] Figure 8 This is a SEM photo obtained by scanning electron microscope on the product obtained in Comparative Example 6 in Test Example 1 of the present invention;

[0032] Fig. 9 The MgAl2O3 calcined at 700°C at different rates in Test Example 1 of the present invention is 2 O 4 SEM photograph of. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0034] At present, infrared detection is a key detection technology that is developing rapidly and poses a great threat to military facilities and weapons and equipment, especially aircraft, ships and combat vehicles with high-power engines. In order to improve the combat and survivability of weapons and equipment, it is of great significance to develop infrared stealth materials. Magnesium aluminum spinel has high hardness, good corrosion resistance, optical isotropy, no birefringence, and high transmittance from ultraviolet to mid-infrared bands. It is a transparent ceramic material with excellent mechanical properties and excellent optical properties, and has important application value. Domestic and foreign research mainly focuses on the preparation of high-performance magnesium aluminum spinel powders with high purity and narrow particle size distribution. It has certain capabilities in infrared stealth, but there is still much room for improvement.

[0035] In view of the above problems, an embodiment of the present invention provides a method for preparing magnesium aluminum spinel micro-nano fibers, comprising the following steps:

[0036] S1. Dissolve aluminum nitrate, magnesium nitrate and citric acid in water, adjust the pH of the resulting solution to 6.5-7.5, react for at least 10 hours, and then concentrate to a viscous sol;

[0037] S2, uniformly mixing the viscous sol-like reactant obtained in S1 with the glacial acetic acid solution of PVP, so that the PVP concentration in the mixed solution is 0.35-0.45 g / mL, to obtain a spinning precursor solution;

[0038] S3, electrospinning the spinning precursor solution at a voltage of 16-18 kV and a needle of 22 # Stainless steel needle, the distance between the needle and the receiving plate is 14-16cm, and MgAl 2 O 4 / PVP composite fiber;

[0039] S4, the MgAl 2 O 4 The / PVP composite fiber was heated to 650-800°C at a rate of 0.8-1.2°C / min and calcined for 2h, and then naturally cooled to room temperature.

[0040] The embodiment of the present invention also provides the use of the magnesium aluminum spinel micro-nano fiber prepared by the above preparation method in infrared stealth material.

[0041] The scheme of the present invention is described below through specific embodiments.

[0042] Example 1

[0043] This embodiment provides a magnesium aluminum spinel micro-nano fiber and a preparation method thereof.

[0044] S1, Al(NO 3 ) 3 9H 2 O、Mg(NO 3 ) 2 6H 2 O and C 6 H 8 O 7 ·H 2 O as raw materials, mixed in a molar ratio of (2:1:4), dissolved in distilled water, and stirred thoroughly until completely dissolved. Ammonia water was added dropwise to adjust the pH of the resulting solution to 7.0, stirred continuously at room temperature for 10 hours, and then placed in a 90°C thermostat to heat and evaporate the water, and concentrated to a viscous sol state;

[0045] S2, taking a certain amount of PVP and completely dissolving it in glacial acetic acid solution to prepare a 0.5 g / mL PVP glacial acetic acid solution, and evenly mixing the viscous sol-like reactant obtained in S1 with the PVP glacial acetic acid solution to make the PVP concentration in the mixed solution 0.4 g / mL, thereby obtaining a spinning precursor solution;

[0046] S3, the spinning precursor solution was transferred into the syringe for electrospinning, the voltage was 17 kV, the needle was 22 # Stainless steel needle, the distance between the needle and the receiving plate is 15cm, MgAl 2 O 4 / PVP composite fiber;

[0047] S4, the MgAl 2 O 4 The / PVP composite fiber was heated to 700°C at a rate of 1.0°C / min, kept at that temperature for 2h, and then naturally cooled to room temperature.

[0048] Example 2

[0049] This embodiment provides a magnesium aluminum spinel micro-nano fiber and a preparation method thereof.

[0050] S1, Al(NO 3 ) 3 9H 2 O、Mg(NO 3 ) 2 6H 2 O and C 6 H 8 O 7 ·H 2 O as raw materials, mixed in a molar ratio of (2:1:4), dissolved in distilled water, and stirred thoroughly until completely dissolved. Ammonia water was added dropwise to adjust the pH of the resulting solution to 7.0, stirred continuously at room temperature for 10 hours, and then placed in a 90°C thermostat to heat and evaporate the water, and concentrated to a viscous sol state;

[0051] S2, taking a certain amount of PVP and completely dissolving it in glacial acetic acid solution to prepare a 0.5 g / mL PVP glacial acetic acid solution, and evenly mixing the viscous sol-like reactant obtained in S1 with the PVP glacial acetic acid solution to make the PVP concentration in the mixed solution 0.4 g / mL, thereby obtaining a spinning precursor solution;

[0052] S3, the spinning precursor solution was transferred into the syringe for electrospinning, the voltage was 17 kV, the needle was 22 # Stainless steel needle, the distance between the needle and the receiving plate is 15cm, MgAl 2 O 4 / PVP composite fiber;

[0053] S4, the MgAl 2 O 4 The / PVP composite fiber was heated to 800°C at a rate of 1.0°C / min, kept at that temperature for 2h, and then naturally cooled to room temperature.

[0054] Example 3

[0055] This embodiment provides a magnesium aluminum spinel micro-nano fiber and a preparation method thereof.

[0056] S1, Al(NO 3 ) 3 9H 2 O、Mg(NO 3 ) 2 6H 2 O and C 6 H 8 O 7 ·H 2 O as raw materials, mixed in a molar ratio of (2:1:4), dissolved in distilled water, and stirred thoroughly until completely dissolved. Ammonia water was added dropwise to adjust the pH of the resulting solution to 7.0, stirred continuously at room temperature for 10 hours, and then placed in a 90°C thermostat to heat and evaporate the water, and concentrated to a viscous sol state;

[0057] S2, taking a certain amount of PVP and completely dissolving it in glacial acetic acid solution to prepare a 0.5 g / mL PVP glacial acetic acid solution, and evenly mixing the viscous sol-like reactant obtained in S1 with the PVP glacial acetic acid solution to make the PVP concentration in the mixed solution 0.4 g / mL, thereby obtaining a spinning precursor solution;

[0058] S3, the spinning precursor solution was transferred into the syringe for electrospinning, the voltage was 17 kV, the needle was 22 # Stainless steel needle, the distance between the needle and the receiving plate is 15cm, MgAl 2 O 4 / PVP composite fiber;

[0059] S4, the MgAl 2 O 4 The / PVP composite fiber was heated to 700°C at a rate of 10°C / min, kept at that temperature for 2h, and then naturally cooled to room temperature.

[0060] Example 4

[0061] This embodiment provides a magnesium aluminum spinel micro-nano fiber and a preparation method thereof.

[0062] S1, Al(NO 3 ) 3 9H 2 O、Mg(NO 3 )2 6H 2 O and C 6 H 8 O 7 ·H 2 O as raw materials, mixed in a molar ratio of (2:1:4), dissolved in distilled water, and stirred thoroughly until completely dissolved. Ammonia water was added dropwise to adjust the pH of the resulting solution to 6.5, stirred continuously at room temperature for 10 hours, and then placed in a 90°C thermostat to heat and evaporate water, and concentrated to a viscous sol state;

[0063] S2, take a certain amount of PVP and completely dissolve it in glacial acetic acid solution to prepare 0.45g / mL PVP glacial acetic acid solution, mix the viscous sol-like reactant obtained in S1 with the PVP glacial acetic acid solution to make the PVP concentration in the mixed solution 0.35g / mL, and obtain a spinning precursor solution;

[0064] S3, the spinning precursor solution was transferred into the syringe for electrospinning, the voltage was 18kV, the needle was 22 # Stainless steel needle, the distance between the needle and the receiving plate is 14cm, MgAl 2 O 4 / PVP composite fiber;

[0065] S4, the MgAl 2 O 4 The / PVP composite fiber was heated to 700°C at a rate of 1.2°C / min, kept at that temperature for 2h, and then naturally cooled to room temperature.

[0066] Example 5

[0067] This embodiment provides a magnesium aluminum spinel micro-nano fiber and a preparation method thereof.

[0068] S1, Al(NO 3 ) 3 9H 2 O、Mg(NO 3 ) 2 6H 2 O and C 6 H 8 O 7 ·H 2 O as raw materials, mixed in a molar ratio of (2:1:4), dissolved in distilled water, and stirred thoroughly until completely dissolved. Ammonia water was added dropwise to adjust the pH of the resulting solution to 7.5, stirred continuously at room temperature for 10 hours, and then placed in a 90°C thermostat to heat and evaporate water, and concentrated to a viscous sol state;

[0069] S2, take a certain amount of PVP and completely dissolve it in glacial acetic acid solution to prepare 0.55g / mL PVP glacial acetic acid solution, mix the viscous sol-like reactant obtained in S1 with the PVP glacial acetic acid solution to make the PVP concentration in the mixed solution 0.45g / mL, and obtain a spinning precursor solution;

[0070] S3, the spinning precursor solution was transferred into the syringe for electrospinning, the voltage was 16kV, the needle was 22 # Stainless steel needle, the distance between the needle and the receiving plate is 16cm, MgAl 2 O 4 / PVP composite fiber;

[0071] S4, the MgAl 2 O 4 The / PVP composite fiber was heated to 700°C at a rate of 0.8°C / min, kept at that temperature for 2h, and then naturally cooled to room temperature.

[0072] Comparative Example 1

[0073] This comparative example provides a magnesium aluminum spinel micro-nano fiber, and its preparation method is basically the same as that of Example 1, except that the PVP concentration in the mixed solution in S2 is 0.3 g / mL.

[0074] Comparative Example 2

[0075] This comparative example provides a magnesium aluminum spinel micro-nano fiber, and its preparation method is basically the same as that of Example 1, except that the PVP concentration in the mixed solution in S2 is 0.5 g / mL.

[0076] Comparative Example 3

[0077] This comparative example provides a magnesium aluminum spinel micro-nano fiber, and its preparation method is basically the same as that of Example 1, except that the temperature is raised to 900° C. in S4.

[0078] Comparative Example 4

[0079] This comparative example provides a magnesium aluminum spinel micro-nano fiber, and its preparation method is basically the same as that of Example 1, except that the temperature is raised to 1000° C. in S4.

[0080] Comparative Example 5

[0081] This comparative example provides a magnesium aluminum spinel micro-nano fiber, and its preparation method is basically the same as that of Example 1, except that the temperature is raised to 1200° C. in S4.

[0082] Comparative Example 6

[0083] This comparative example provides a magnesium aluminum spinel micro-nano fiber, and its preparation method is basically the same as that of Example 1, except that the temperature is raised to 1500° C. in S4.

[0084] Comparative Example 7

[0085] This comparative example provides a magnesium aluminum spinel micro-nano fiber, and its preparation method is basically the same as that of Example 1, except that the heating rate in S4 is 50° C. / min.

[0086] Comparative Example 8

[0087] This comparative example provides a magnesium aluminum spinel micro-nano fiber, and the preparation method thereof is basically the same as that of Example 1, except that the heating rate in S4 is 100° C. / min.

[0088] Comparative Example 9

[0089] This comparative example provides a magnesium aluminum spinel micro-nano fiber, and its preparation method is basically the same as that of Example 1, except that the distance between the needle and the receiving plate in S3 is 13 cm.

[0090] Comparative Example 10

[0091] This comparative example provides a magnesium aluminum spinel micro-nano fiber, and its preparation method is basically the same as that of Example 1, except that the distance between the needle and the receiving plate in S3 is 17 cm.

[0092] Comparative Example 11

[0093] This comparative example provides a magnesium aluminum spinel micro-nano fiber, and its preparation method is basically the same as that of Example 1, except that the voltage in S3 is 15 kV.

[0094] Comparative Example 12

[0095] This comparative example provides a magnesium aluminum spinel micro-nano fiber, and its preparation method is basically the same as that of Example 1, except that the voltage in S3 is 19 kV.

[0096] Test Example 1

[0097] In this test example, the MgAl prepared in Example 1 was firstly subjected to the test using a differential thermal-thermogravimetric instrument SDT-Q600 from TA, USA. 2 O 4 / PVP composite fibers were subjected to DSC-TGA analysis.

[0098] The DSC-TGA analysis results are as follows Figure 1 As shown, MgAl 2 O 4The thermal decomposition process of PVP / PVP composite fibers can be roughly divided into the following stages: the first stage is from room temperature to 130°C, with a weight loss rate of about 14.89% on the TGA curve, corresponding to an endothermic peak near 80°C on the DSC curve, which is due to the volatilization of water adsorbed on the surface of the composite fibers and residual solvents; the second stage is from 130 to 320°C, with a weight loss rate of about 8.63%, corresponding to a small exothermic peak near 310°C on the DSC curve, which is caused by the partial oxidation and decomposition of inorganic salts; the third stage is from 320 to At 650℃, a large weight loss step appeared on the TGA curve, and the weight loss rate was about 75.44%, corresponding to an endothermic peak near 440℃ on the DSC curve, which was mainly caused by the decomposition of the spinning aid PVP and the complete oxidation of the inorganic salts; when the temperature exceeded 650℃, the TGA curve tended to be horizontal, and the weight loss rate basically did not change, indicating that the thermal decomposition process of the composite fiber was completed, and the PVP, nitrate, acetate groups, residual solvents and other volatiles contained in it had been removed, indicating that the pure spinel structure of MgAl 2 O 4 form.

[0099] To clarify MgAl 2 O 4 Does the PVP composite fiber form MgAl after heat treatment? 2 O 4 In this test example, the XD6 polycrystalline X-ray diffractometer of Beijing Puxi was used to perform phase (XRD) analysis on the composite fiber after heat treatment at different temperatures in Examples 1 and 2 and Comparative Examples 3 to 6. The X-ray diffraction results are shown in Figure 2 As shown, MgAl 2 O 4 / PVP composite fiber is in an amorphous state before calcination, and is an inorganic salt without a crystalline structure. After calcination at 700°C (Example 1) and above (Example 2, Comparative Examples 3 to 6), the same as MgAl 2 O 4 Compared with the standard PDF card (PDF No: 21-1152), the obtained products are all the same as the standard MgAl 2 O 4 The diffraction peaks of the composite fibers are the same, indicating that after the composite fibers are calcined at a temperature above 700 °C, the product is a single MgAl 2 O 4 phase, which is consistent with the analysis results of DSC-TGA. 2 O 4 The intensity of each diffraction peak of MgAl / PVP composite fiber is still relatively weak, and the peak shape is relatively wide, indicating that the crystallinity of the product at this temperature is not high and the grain size is relatively small. With the increase of calcination temperature, the intensity of each diffraction peak gradually increases and the peak shape becomes narrower, which indicates that MgAl2 O 4 The crystallinity of the grains is increasing, the crystal structure is becoming more complete, but the size is gradually increasing.

[0100] To further verify the MgAl 2 O 4 The structural characteristics of the micro-nano fibers were analyzed by using Nicolet-380 Fourier transform infrared spectrometer from Nicolet, USA, to analyze the MgAl2O3 obtained by calcining at 700°C in Example 1. 2 O 4 The micro-nano fibers were analyzed by infrared spectroscopy (FT-IR). Figure 3 The calcined product is at 3450cm -1 and 1637cm -1 The stretching vibration absorption peak attributable to the OH bond of water molecules was observed near 1403 cm -1 The absorption peak at is attributed to CO 3- stretching vibration, which is the product of the adsorption of water and CO in the air 2 The absorption peak produced by the reaction; the product is at 691cm -1 and 510cm -1 The absorption peaks near the metal-oxygen ion (MO) bond and [AlO 6 ] stretching vibration peak of Al-O bond in octahedron; and 2351cm -1 The absorption peak at is due to the propagation of infrared light in the air. In addition to the above peaks, there are basically no other absorption peaks in the spectrum, which further illustrates that MgAl 2 O 4 After calcination at 700℃, the metal inorganic salts and PVP in the composite fiber were completely decomposed to generate the target MgAl 2 O 4 .

[0101] This test example also used a KYKY-6200 scanning electron microscope produced by Beijing Zhongke Instrument to observe the MgAl prepared by electrospinning of the precursor spinning solutions with different PVP mass concentrations in Example 1 and Comparative Examples 1 and 2. 2 O 4 The microstructure (SEM) of the PVP / PVP composite fibers before calcination (i.e., S3) is shown in Figure 4 When the mass concentration of PVP is 0.3 g·mL -1 When (Comparative Example 1), there are a large number of "spindles" in the composite fiber, as shown in Figure 4 Figure (a); As the PVP concentration increases, the "spindles" in the composite fibers gradually disappear. When the mass concentration of PVP increases to 0.4 g mL-1 When (Example 1), the composite fiber is round and has a smooth surface, and the fiber diameter is mainly distributed between 200 and 700 nm. Figure 4 Figure (b) in Figure 2. However, when the mass concentration of PVP increases to 0.5 g·mL -1 When (Comparative Example 2), the thickness of the composite fiber is uneven, and adhesion occurs. Figure 4 Figure (c) in the figure. It can be seen that the PVP concentration has a great influence on the formation of composite fibers. The reasons for the above phenomenon may be: when the PVP concentration is low, a large number of solvent molecules and fewer PVP chains are cross-linked, and the shape of the spinneret is mainly maintained by surface tension, so it is difficult to maintain its continuity, and small spray droplets will be formed, which leads to more "spindles" in the composite fiber. With the increase of PVP concentration, the solvent molecules in the precursor spinning solution will cross-link with more PVP chains. The charge on the spinneret can completely stretch the spinneret when the solvent molecules are distributed between the PVP polymer chains, and obtain fibers with smooth surface and uniform thickness; but when the PVP concentration continues to increase, secondary spinnerets are generated during the electrospinning process and separated from the main spinnerets, making the fiber diameter uneven. At the same time, the high PVP concentration slows down the evaporation rate of the solvent during the spinning process, which makes it easy for the fibers to stick together. In this experiment, the mass concentration of PVP is 0.4g·mL -1 Electrospinning of MgAl 2 O 4 / PVP composite fiber has better morphology.

[0102] Figures 5 to 9 MgAl in Example 2, Comparative Example 3, Comparative Example 5 and Comparative Example 6 2 O 4 SEM photos of the PVP / PVP composite fibers after calcination at 800°C, 900°C, 1000°C, 1200°C and 1500°C. Figure 5 ), the obtained product still maintains a good continuous fibrous structure, which indicates that PVP plays a template role in the entire formation process of the product, but due to the complete decomposition of PVP, the inorganic salt is oxidized and removed, and the fiber diameter is greatly reduced; after calcination at 900 ° C (Comparative Example 3, Figure 6 ), due to the increase of calcination temperature, MgAl 2 O 4 The grains grow, and the adjacent fibers "bend" and "melt" at the same time. The product loses its fibrous morphology and presents a three-dimensional network. As the calcination temperature increases again, MgAl 2 O 4 As the grains continue to fuse and grow, some large grains "swallow" some small grains, which intensifies the "melting" phenomenon. Figure 7(Comparative Example 5) It can be seen that after calcination at 1200°C, the "devouring" effect between the grains becomes more intense due to the higher energy, some grains grow abnormally, and the product presents a mixed morphology of hills and grains; when calcined at a higher temperature of 1500°C (Comparative Example 6), the product is all granular MgAl 2 O 4 ,See Figure 8 .

[0103] Fig. 9 MgAl in Example 3, Comparative Examples 7 and 8 2 O 4 / PVP composite fiber at 10℃·min -1 、50℃·min -1 and 100℃·min -1 SEM photos of MgAl after calcination at 700℃. It can be seen that with the increase of heating rate, 2 O 4 will appear in the form of curved short fibers ( Fig. 9 Figure a), hilly ( Fig. 9 b) and granular ( Fig. 9 The formation of these morphologies is related to crystal growth. At a slower heating rate (Example 1, 1 ° C·min -1 ) under the condition that atoms can fully diffuse, the nucleus formation process becomes longer, and the grains can fully develop, so that the crystal can fully grow along the one-dimensional axial direction. When organic matter, inorganic salts, etc. are completely oxidized and decomposed under high temperature calcination, the product maintains a fibrous morphology (see Figure 5 ); when the heating rate is faster (Example 3, 10℃·min -1 ), the crystal can still grow along the one-dimensional axial direction, but the rate of oxidative decomposition of organic matter and inorganic salts is accelerated, and the diameter of the product shrinks significantly in a short period of time, causing the fiber to break and form a curved short fiber; when the heating rate is faster (Comparative Example 7, 50℃·min -1 ), the crystal nuclei are generated rapidly, the generated nanocrystals have large surface energy, tend to aggregate with each other, and the adjacent grains fuse and "swallow" each other and grow, so the product presents a hilly shape; when the heating rate is very fast (Comparative Example 8, 100℃·min -1 ), after the crystal nucleus is formed, spherical equiaxed crystals are formed more rapidly with the crystal nucleus as the center, so the product presents a granular morphology.

[0104] Test Example 2

[0105] This test example provides the infrared emissivity of the magnesium aluminum spinel micro-nano fibers prepared in the above examples and the products prepared in the comparative examples.

[0106] The final products obtained in each embodiment and comparative example were uniformly mixed with epoxy resin and curing agent (the volume ratio of the final product to the epoxy resin was 1:1, and the volume ratio of the resin to the curing agent was 10:1), dispersed uniformly by a microwave oscillator, uniformly coated on an aluminum sheet, dried at 100°C for 12 hours in a vacuum drying oven, and then cooled to room temperature to obtain a test coating. The infrared emissivity of the above coating was tested using the IR-2 dual-band emissivity tester of Shanghai Lightwave Technology Co., Ltd. The results are shown in Table 1:

[0107] Table 1 Infrared emissivity (n=5)

[0108]

[0109]

[0110] Note: * indicates P < 0.05 compared with Example 1.

[0111] Example 6

[0112] This embodiment provides the application of magnesium aluminum spinel micro-nano fibers in the preparation of infrared stealth coatings. The infrared stealth coatings are prepared by conventional methods using magnesium aluminum spinel micro-nano fibers prepared in Examples 1 to 5 and components commonly used in the coating field as raw materials.

[0113] Example 7

[0114] This embodiment provides the application of magnesium aluminum spinel micro-nano fibers in the preparation of infrared stealth film. The infrared stealth film is prepared by conventional methods using magnesium aluminum spinel micro-nano fibers prepared in Examples 1 to 5 and components commonly used in the film field as raw materials.

[0115] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing magnesium aluminum spinel micro-nano fibers, characterized in that: The following steps are involved: S1. Dissolve aluminum nitrate, magnesium nitrate and citric acid in water, adjust the pH of the resulting solution to 6.5-7.5, react for at least 10 hours, and then concentrate to a viscous sol; S2, uniformly mixing the viscous sol-like reactant obtained in S1 with the glacial acetic acid solution of PVP, so that the PVP concentration in the mixed solution is 0.35-0.45 g / mL, to obtain a spinning precursor solution; S3, electrospinning the spinning precursor solution at a voltage of 16-18 kV and a needle of 22 # A stainless steel needle, the distance between the needle and the receiving plate is 14-16 cm, and MgAl2O4 / PVP composite fibers are obtained; S4. The MgAl2O4 / PVP composite fiber is heated to 650-800°C at a rate of 0.8-1.2°C / min and calcined for 2 hours, and then naturally cooled to room temperature.

2. The preparation method according to claim 1, characterized in that: The molar ratio of aluminum nitrate, magnesium nitrate and citric acid is 2:1:

4.

3. The preparation method according to claim 1, characterized in that: In S1, the pH of the resulting solution is adjusted with aqueous ammonia.

4. The preparation method according to any one of claims 1 to 3, characterized in that: The PVP concentration in S2 was 0.4 g / mL.

5. The preparation method according to any one of claims 1 to 3, characterized in that: The voltage in S3 was 17 kV and the distance between the needle and the receiving plate was 15 cm.

6. The preparation method according to any one of claims 1 to 3, characterized in that: The calcination temperature in S4 is 650-750°C.

7. A magnesium aluminum spinel micro-nano fiber, characterized in that: The method is prepared according to any one of claims 1 to 6.

8. Use of the magnesium aluminum spinel micro-nano fiber according to claim 7 in the preparation of infrared stealth materials.

9. An infrared stealth material, characterized in that: The raw material includes the magnesium aluminum spinel micro-nano fiber as claimed in claim 7.

10. The infrared stealth material according to claim 9, characterized in that: The infrared stealth material includes a film and a coating.